NILAI-NILAI AJARAN HASTABRATA DALAM LAOKONPEWAYANGAN MAKUTHARAMA SEBAGAI MEDIA MEMBANGUN KARAKTER BANGASA - suhari suhari suhari (Universitas PGRI Adi Buana Surabaya, 2014)
The Doctrine of Hastabrata is eight behaviors or eight characters that should be run by someone who serves as leader base done elements derived from nature. Although there are different interpretations, but it is commonly a natural element: Surya (sun); Chandra (Moon); Sudama (Star); Maruta/Angin (moving air); Mendhung (rain clouds); Dahana (Fire); Tirta/Samudra (Water); Pratala (Land); More value is owned of Hastabrata doctrine rooted in the natural elements. It can be applied in the context of the formation of character to anyone, especially the position as leader and the led.Keywords: value, hastabrata, character.